The Impact of Citrus-Tea Cofermentation Process on Chemical Composition and Contents of Pu-Erh Tea: An Integrated Metabolomics Study - Xu, Ya; Liang, Pu-Lin; Chen, Xue-Lian; Gong, Ming-Jiong; Zhang, Liang; Qiu, Xiao-Hui; Zhang, Jing; Huang, Zhi-Hai; Xu, Wen (Frontiers in Nutrition, 2021)
Ganpu tea, an emerging pu-erh compound tea, which is co-fermented with the peel of Citrus reticulata ‘Chachi’, has been widely favored by Chinese consumers due to its potential health effects and distinct flavor and taste. So far, the influence of this co-fermentation procedure on the chemical profile of pu-erh tea has barely been addressed yet. In this work, an ultra-high-performance liquid chromatography-Q Exactive Orbitrap mass spectrometry (UHPLC-QE Orbitrap MS)-based qualitative and quantitative method combined with multivariate analysis was conducted to comprehensively investigate the chemical changes in pu-erh tea after co-fermented with Citrus peel. A total of 171 compounds were identified based on a three-level strategy, among which 7 phenolic acids, 11 flavan-3-ols, 27 flavonoids and flavonoid glycosides were identified from pu-erh tea for the first time. 89 main constituents were selected for further quantitative analysis using a validated method. Both the PCA of untargeted metabolomics and OPLS-DA models of targeted components revealed the significant chemical profile disparity between the raw pu-erh tea and Ganpu tea. It showed that Citrus-tea co-fermentation process significantly decreased the total contents of phenolic acids, flavan-3-ols and flavonoid aglycones, while most of the quercetin glycosides and myricetin glycosides as well as the vitexin were significantly increased. In addition, hesperidin, a flavonoid glycoside only existed in Citrus, was first found in pu-erh tea after co-fermented with Citrus. This study clearly profiled the chemical composition and content changes of pu-erh tea after co-fermented with Citrus peel, which revealed that Citrus-tea co-fermentation process further accelerated the fermentation of pu-erh tea and improved the unique flavor of tea.